2021
DOI: 10.1101/2021.08.25.457671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel multifunctional role for Hsp70 in binding post-translational modifications on client proteins

Abstract: Hsp70 interactions are critical for cellular viability and the response to stress. Previous attempts to characterize Hsp70 interactions have been limited by their transient nature and inability of current technologies to distinguish direct vs bridged interactions. We report the novel use of cross-linking mass spectrometry (XL-MS) to comprehensively characterize the budding yeast Hsp70 protein interactome. Using this approach, we have gained fundamental new insights into Hsp70 function, including definitive evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…It makes intuitive sense, however, that the septin NC interface, which at least for Cdc11 and Shs1 is exposed at both ends of a septin octamer, would not attract much cytosolic chaperone attention. A recent study that crosslinked Lys residues (Nitika et al, 2021) found a direct interaction between Ssa1 and a Lys (478) in the CTE of Cdc3, far from the G and NC interfaces (Supplemental Figure 9) and within the putative coiled coil formed in the non-native G Cdc3 homodimer (Figure 1). These crosslinks with Ssa1 probably only occurred because the other Ssa chaperones were eliminated (Nitika et al, 2021), otherwise Ssa2, Ssa3 or Ssa4 would presumably have "outcompeted" Ssa1 for septin interaction.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It makes intuitive sense, however, that the septin NC interface, which at least for Cdc11 and Shs1 is exposed at both ends of a septin octamer, would not attract much cytosolic chaperone attention. A recent study that crosslinked Lys residues (Nitika et al, 2021) found a direct interaction between Ssa1 and a Lys (478) in the CTE of Cdc3, far from the G and NC interfaces (Supplemental Figure 9) and within the putative coiled coil formed in the non-native G Cdc3 homodimer (Figure 1). These crosslinks with Ssa1 probably only occurred because the other Ssa chaperones were eliminated (Nitika et al, 2021), otherwise Ssa2, Ssa3 or Ssa4 would presumably have "outcompeted" Ssa1 for septin interaction.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study that crosslinked Lys residues (Nitika et al, 2021) found a direct interaction between Ssa1 and a Lys (478) in the CTE of Cdc3, far from the G and NC interfaces (Supplemental Figure 9) and within the putative coiled coil formed in the non-native G Cdc3 homodimer (Figure 1). These crosslinks with Ssa1 probably only occurred because the other Ssa chaperones were eliminated (Nitika et al, 2021), otherwise Ssa2, Ssa3 or Ssa4 would presumably have "outcompeted" Ssa1 for septin interaction. As the crosslinked lysine in Ssa1 lies on the surface of the lid of the substrate-binding domain, it is possible that, once the Cdc3 NTE is displaced by interaction with Cdc12, the Ssa1 substrate-binding pocket does engage the Cdc3 G interface, bringing the Lys-rich Cdc3 CTE near the Ssa1 lid (Supplemental Figure 9).…”
Section: Discussionmentioning
confidence: 91%
“…A challenge in understanding the differential role of the Ssa paralogs is a lack of verified client proteins. While several Hsp70 interactomes have been published under differing conditions and phosphorylation site mutations, validation of these and their cellular effect is still under investigation [33, 4347]. Excellent attempts to dissect the roles of Ssa paralogs include the well-established Hsp90 client (Ste11) and a non-yeast client, v-Src in addition to the yeast prions [ URE3 ] and [ PSI + ] [21].…”
Section: Discussionmentioning
confidence: 99%
“…A challenge in understanding the differential role of the Ssa paralogs is a lack of verified client proteins. While several Hsp70 interactomes have been published under differing conditions and phosphorylation site mutations, validation of these and their cellular effect is still under investigation [ 37 , 47 51 ]. Excellent attempts to dissect the roles of Ssa paralogs include the well-established Hsp90 client (Ste11) and a non-yeast client, v-Src in addition to the yeast prions [ URE3 ] and [ PSI + ] [ 23 , 25 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%